Spectra of heat and momentum fluxes over the east coast of India during MONEX-1979 (MAUSAM, 1987)
The heat and momentum fluxes at the eastern coast of Indian Peninsula have been, computed for the MONEX-79, May through August. The spectral analyses of these fluxes were performed. Oscillations of short and medium range periodicity in momentum fluxes were observed. The mean eddy sensible heat and mean eddy latent heat flux show opposite variations in periodicity with latitude.